Hybrid mesoporous microbeads based on sheets-like sulfur-doped copper oxide embedded in calcium alginate-derived carbon for batch and columnar adsorption of cationic dye - Naggar, Ahmed H.; Alshammari, Mutairah S.; Seaf-Elnasr, Tarek A.; Chong, Kwok Feng; Bakr, Zinab H.; Alotaibi, N. F.; Ali, Hazim M.; El-Nasser, Karam S.; Thabet, Mahmoud; Abd El-Monaem, Eman M.; Goda, Adel E. S.; Gomaa, Hassanien (Elsevier Ltd, 2024)
Recent increases in the release of untreated water containing cationic dyes have led to significant environmental issues in ecosystems. Many industries contribute to this pollution by discharging water containing various organic pollutants, including crystal violet (CV). Therefore, a novel hybrid mesoporous sulfur-doped copper oxide embedded in Cu-alginate-derived carbon micro-beads (SCO@CACBs) adsorbent was developed for CV-decolorization through batch and fixed-bed columnar techniques. Comparative studies on the effectiveness of CV removal using CACBs and SCO@CACBs under different conditions such as pH, stirring time, amount of sorbent, initial CV concentration, and temperature were conducted. The results demonstrated that the optimal CV removal reached up to 99 % at neutral pH conditions (pH of 7), with an adsorption capacity of 87 mg/g through a batch approach. The CV adsorption process was analyzed using various methods, including adsorption isotherms, kinetics, thermodynamics, zeta potential measurements, and density-functional theory (DFT) calculations. Langmuir (R2 = 0.995) and pseudo 2nd order (R2 = 0.998) models most agree with experimental CV-adsorption data. Thermodynamic parameters indicated that CV adsorption is spontaneous, favorable, and endothermic. The columnar adsorption tests showed that the adsorption capacity of SCO@CACBs varied from 83.6 to 71.3 mg/g as the flow rate varied from 2 to 6 mL/min and 81.5–115.6 mg/g as the adsorbent mass varied from 1 to 4 g. The Thomas and Yoon-Nelson models fitted the breakthrough curves. The adsorbent maintained high removal efficiency (about 93 %) after five reuse cycles through batch and fixed-bed columnar approaches. Notably, the SCO@CACBs showed over 96 % efficiency in removing CV dye from actual agricultural and textile wastewater samples using batch and column setups. Thus, SCO@CACBs is an effective sorbent for removing CV dye from water contaminated by natural sources.